The Educational Effects of Hadiths about Seeking Refuge from the Evil Eye and Envy and Ways to Protect Oneself/ An analytical educational - Nagham Mohammed Sameer,; Abdullah Kareem Elawi, (Islamic Sciences Journal, 2025)
This research deals with the importance of a person resorting to Allah Almighty and seeking refuge in Him from the evil eyes of envious and spiteful humans and jinn, who do not hope for good for others, and the many organic, psychological and physical diseases caused by their eyes. The Prophet (peace and blessings of Allah be upon him) sought refuge in many hadiths from the evil eye and envy so that Muslims may follow his example in protecting themselves and their children, just as the Prophet (peace and blessings of Allah be upon him) protected his two grandsons, Hassan and Hussein, peace be upon them, with supplications and remembrances. This research sheds light on the hadiths of seeking refuge from the evil eye and envy, and explains the educational effects of those hadiths through what was mentioned of prophetic hadiths in which the Prophet (peace and blessings of Allah be upon him) sought refuge from the evils of envious and spiteful devils among humans and jinn.